Racial and Ethnic Differences in Knowledge About One's Dementia Status. Issue 8 (13th April 2020) - Lin, Pei‐Jung; Emerson, Joanna; Faul, Jessica D.; Cohen, Joshua T.; Neumann, Peter J.; Fillit, Howard M.; Daly, Allan T.; Margaretos, Nikoletta; Freund, Karen M.
Abstract : OBJECTIVES: To examine racial and ethnic differences in knowledge about oneʼs dementia status. DESIGN: Prospective cohort study. SETTING: The 2000 to 2014 Health and Retirement Study. PARTICIPANTS: Our sample included 8, 686 person‐wave observations representing 4, 065 unique survey participants, aged 70 years or older, with dementia, as identified by a well‐validated statistical prediction model based on individual demographic and clinical characteristics. MEASUREMENTS: Primary outcome measure was knowledge of oneʼs dementia status, as reported in the survey. Patient characteristics included race/ethnicity, age, sex, survey year, cognition, function, comorbidity, and whether living in a nursing home. RESULTS: Among subjects identified as having dementia by the prediction model, 43.5% to 50.2%, depending on the survey year, reported that they were informed of the dementia status by their physician. This proportion was lower among Hispanics (25.9%‐42.2%) and non‐Hispanic blacks (31.4%‐50.5%) than among non‐Hispanic whites (47.7%‐52.9%). Our fully adjusted regression model indicated lower dementia awareness among non‐Hispanic blacks (odds ratio [OR] = 0.74; 95% confidence interval [CI] = 0.58‐0.94) and Hispanics (OR = 0.60; 95% CI = 0.43‐0.85), compared to non‐Hispanic whites. Having more instrumental activity of daily living limitations (OR = 1.65; 95% CI = 1.56‐1.75) and living in a nursing home (OR = 2.78; 95% CI = 2.32‐3.32) were associated with increased odds of subjects reporting being told about dementia by a physician. CONCLUSION: Less than half of individuals with dementia reported being told by a physician about the condition. A higher proportion of non‐Hispanic blacks and Hispanics with dementia may be unaware of their condition, despite higher dementia prevalence in these groups, compared to non‐Hispanic whites. Dementia outreach programs should target diverse communities with disproportionately high disease prevalence and low awareness. J Am Geriatr Soc 68:1763‐1770, 2020.